Mrs. John A. Johnson and Mrs. Will Perry at the lake (Nicollet County Historical Society, 1851 North Minnesota Avenue, St. Peter, MN 56082; http://www.nchsmn.org, 1898)
794120a6611f43c0c6b72f22ecf2e92e
This photo shows Mrs. John A. Johnson (at left) and Mrs. Will Perry, both from St. Peter, in bathing costumes at an area lake, probably Lake Emily east of St. Peter. Mrs. Johnson's husband, John A. Johnson, served as the governor of Minnesota from 1905 until 1909.
United States
Minnesota
Le Sueur
Kasota Township
Mode of access: Internet.
Keywords: Mrs. John A. Johnson; Women; Clothing and dress; Lakes & ponds; Bathing suits; Sports and Recreation